Synthesis of ZnO Nanoparticles from Zink Acetate using Red Betel and Bay Leaves Extract and It’s Application as Sunscreen - Karim Theresih; Cornelia Budimarwanti; Indyah Sulistyo Arty; Sri Handayani; Novia Putri Ramadhani; Rakhmawati Kurniasih (Indonesian Journal of Chemistry and Environment, 2021)
The ZnO nanoparticles have been synthesized using red betel and bay leaves extract and characterized to analyze the maximum wavelength, crystallinity, particle size, composition, and its activity as sunscreen. The synthesis of ZnO nanoparticles was carried out through reflux method using Zn(CH3COO)2. 2H2O red betel leaf as bioreductor. The same procedure was also applied by changing the betel leaf extract with bay leaf extract. The resulted materials were characterized by UV-Vis spectrophotometry, FTIR, PSA, XRD, and SEM EDX. The ZnO nanoparticles synthesized with red betel leaf have a maximum wavelength of 374.5 nm, wave number of 462.92 cm-1, particle size of 23.309 nm, 74.1% of Zn and 16% of O, SPF value of 8.047942. ZnO nanoparticles synthesized using bay leaf extract have a maximum wavelength of 374 nm, high crystallinity properties with a hexagonal crystal structure, an average particle size of 2.463 nm, 64.21% of Zn and 22.85%, and an SPF value of 2.886969. The activity test of ZnO nanoparticles as sunscreen showed that synthesis both using red betel and by leaves extract resulted in a good sunscreen activity test comparing with ZnO synthesized using ethanol as a control. Thus the synthesis of ZnO nanoparticles using natural extract is being a better way to use as a green synthesis that environmentally friendly.